Supernumerary chromosome inheritance in the curimbata (Prochilodus lineatus) of the Mogi-Guacu River - Voltolin, Tatiana Aparecida; Senhorini, Jose Augusto; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP]; Bortolozzi, Jehud; Porto-Foresti, Fábio [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
Prochilodus lineatus is widely used in pisciculture projects, mainly in the south of Brazil. It shows a basic karyotype composed of 2n = 54 chromosomes, in addition to as many as seven supernumerary chromosomes, also known as B-chromosomes. These additional small chromosomes are frequently heterochromatic, vary in number and morphology, and generally have no homology with the A complement. Intensive studies have investigated the function, origin and inheritance of these supernumerary chromosomes. The present study aimed to determine the inheritance pattern of the B-chromosomes resulting from directed cross-fertilization of P. lineatus, Prochilodontidae isolated from the Mogi-Guacu River, Pirassununga, SP. These cross-fertilization experiments were performed at CEPTA/ICMBio in Pirassununga. The transmission patterns of these micro-chromosomes agreed (K(B) = 0.48) with the expectation of regular meiotic behavior following a Mendelian transmission model (K(B) = 0.5). A non-accumulation process was observed for these B-chromosomes in filial generations. Together, our results indicate that the supernumerary chromosomes in P. lineatus samples from the Mogi-Guacu River exist in a neutral state and follow a Mendelian inheritance pattern.